23-valent pneumococcal polysaccharide vaccine improves survival in dialysis patients by preventing cardiac events. Issue 43 (8th October 2019) - Ihara, Hiroaki; Kikuchi, Kan; Taniguchi, Hiromi; Fujita, Shogo; Tsuruta, Yuki; Kato, Motoyasu; Mitsuishi, Yoichiro; Tajima, Ken; Kodama, Yuzo; Takahashi, Fumiyuki; Takahashi, Kazuhisa; Azuma, Nakanobu
Abstract: Background: Immunodeficient patients are recommended to receive pneumococcal vaccination. However, there is limited evidence showing effectiveness of the polysaccharide vaccine. Polysaccharide vaccination has shown an association with cardiovascular event risk reduction. We assessed the efficacy of the 23-valent pneumococcal polysaccharide vaccine (PPSV23) in relation to the risk of hospitalization and death due to pneumonia and acute cardiac events. Methods: The medical records of all dialysis patients attending our 8 study centers in 2010 were studied, and we selected 1038 consecutive patients. One-to-one propensity score matching was used to correct for potential selection bias in a PPSV23-vaccinated group versus a non-vaccinated group, and a total of 510 patients were identified for outcome analysis. Time to first admission, or deaths due to all-cause pneumonia or cardiac events until 2015 were compared between both groups. Results: The all-cause death rate was significantly decreased in the PPSV23-vaccinated group, (hazard ratio [HR] 0.62, 95% confidence interval [CI]; 0.46–0.83, P = 0.002). All-cause death was considered to be a competing risk for the other outcomes. Further outcomes were evaluated by competing risk analysis adjusting for mortality. There was no statistically significant difference in the hospitalization rate for pneumonia; however, the hospitalization rate due to cardiac events was significantly lower in the PPSV23-vaccinated group than in the non-vaccinated group (HR 0.44, 95% CI; 0.20–0.96, P = 0.040). There was no statistically significant difference in the death rate due to pneumonia; however, the rate of cardiac death was significantly lower in the PPSV23-vaccinated group than in the non-vaccinated group (HR 0.36, 95% CI; 0.18–0.71, P = 0.003). Conclusions: The PPSV23 vaccination is associated with a good prognosis and a low-risk of cardiac events in dialysis patients; however, there was no evidence indicating enhanced protective efficacy against pneumonia, suggesting the PPSV23 vaccination might improve the prognosis by directly preventing cardiovascular events.